2021
DOI: 10.1038/s41467-021-23154-4
|View full text |Cite
|
Sign up to set email alerts
|

Covalency does not suppress O2 formation in 4d and 5d Li-rich O-redox cathodes

Abstract: Layered Li-rich transition metal oxides undergo O-redox, involving the oxidation of the O2− ions charge compensated by extraction of Li+ ions. Recent results have shown that for 3d transition metal oxides the oxidized O2− forms molecular O2 trapped in the bulk particles. Other forms of oxidised O2− such as O22− or (O–O)n− with long bonds have been proposed, based especially on work on 4 and 5d transition metal oxides, where TM–O bonding is more covalent. Here, we show, using high resolution RIXS that molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 35 publications
4
84
2
Order By: Relevance
“…The interval between two vibrated peaks for both materials is 0.2 eV, indicating that the products of local O 2 are generated in both materials. [ 49–51 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interval between two vibrated peaks for both materials is 0.2 eV, indicating that the products of local O 2 are generated in both materials. [ 49–51 ]…”
Section: Resultsmentioning
confidence: 99%
“…The interval between two vibrated peaks for both materials is 0.2 eV, indicating that the products of local O 2 are generated in both materials. [49][50][51] Operando differential electrochemical mass spectrometry (DEMS) exhibits the oxygen release in the first charge and discharge process for LMNO and LMNPO-V O (Figure 4i,j). The capacity when O 2 begins to release for LMNPO-Vo is higher than that for LMNO.…”
Section: Tm and O Redoxmentioning
confidence: 99%
“…In NaCr 2/3 V 1/3 S 2 case, the integrated XANES area ratio fluctuates around 100 ± 4% (Figure S7, Supporting Information), and the fully discharged sample returned to 100% of the pristine state when integrated from 2465 to 2480 eV, which showed more reversible nature than previous reports on oxygen redox. Except for O K‐edge XAS areas, commonly, the pre‐edge peak intensity or the K‐edge slope show obvious irreversible changes after being fully discharge, [ 1a,b,d,21 ] indicating the changes in electronic structure and variation of local chemical environment for oxides.…”
Section: Resultsmentioning
confidence: 99%
“…[44] Recently, House et al reported 4d and 5d Li-rich O-redox cathodes with covalent interaction still exhibit TM migration, voltage hysteresis and formation of O 2 . [21] To explain the differences in theoretical prediction and experimentally observed anion dimer formation, here, we analogize 4d and 5d Li-rich O-redox cathodes to transition metal sulfides. In previous reports, general transition metal chalcogenides are considered as highly covalent, but the hole concentration on anions that can be stabilized by covalency is related to the extent of covalent interaction, when the concentration exceed the limit of stabilization, catenation of anions would leads to polymerization of the anions.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research effort has been devoted to improve the photo-catalytic efficiency of existing semiconductor materials by applying top down and bottom up nano-engineering approaches [ 5 ]. Major improvements have been achieved by increasing the complexity of the materials at the nanoscale, favouring local charge separation and directing the systems towards specific reaction pathways [ 6 , 7 ]. One area of particular interest is plasmon enhanced catalysis, where only a few examples relevant to hydrogen evolution photo-chemistry have been explored [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%